3.5 Ghz Patch Microstrip Antena Design Using Cst Studio Suite 2019 Software - Arniz Nagia, Aliyah (Politeknik Negeri Padang, 2025)
Design, simulation, fabrication, and analysis of 3.5 GHz Microstrip Patch is a microstrip antenna building that has a small size and is simple. In today's era, microstrip patch antennas play an important role and are very useful because they are compact, easy to integrate, and lightweight. Therefore, quite a lot of people use it. This antenna is designed to operate in the frequency range of 3.4-3.6 GHz. This antenna is usually applied to satellite communications, radar communications, military, and smartphones. Microstrip antenna design is done by using three methods, namely simulation, measurement, and fabrication. The simulation method is software from design using CST STUDIO SUITE 2019 software, the measurement method is using Network Analyzer software, and for fabrication method is the result of antenna design done on PCB. From the simulation results of the 3.5 GHz microstrip antenna design using CST STUDIO SUITE 2019, antenna parameters such as Radiation Pattern, VSWR, and Return Loss were obtained. When fabricating, it is recommended that PCB cuts must be equilateral because this affects the measurement results, and when soldering must be careful and careful so that the results at the time of fabrication are not much different from the results during simulation in CST. If an error occurs during fabrication, the fabricated antenna fails due to lack of accuracy and caution in fabrication.